FENOMENA LAW OF ATTRACTION DI MEDIA SOSIAL DAN PENGARUHNYA TERHADAP RELIGIUSITAS GENERASI Z MUSLIM - Almaidah Yanthi Daulay; M. Syukri Azwar Lubis (Jurnal Bilqolam Pendidikan Islam, 2025)
The Law of Attraction phenomenon is very popular on Indonesian social media, including among Muslim Generation Z. This concept believes that positive thoughts can create reality and manifest desires. This study aims to analyze the spread of this phenomenon, the reasons for Muslim Generation Z's interest, and its influence on their level of religiosity.This research uses a mixed methods approach (quantitative & qualitative). A survey was conducted on 380 respondents from Muslim Generation Z aged 16-24 in Medan City, along with in-depth interviews with 15 informants and analysis of 100 Law of Attraction contents on Instagram, TikTok, and YouTube. Data collection took place from January to March 2024. The results show 82.1% of respondents have seen Law of Attraction content on social media. 47.4% have practiced it in their daily lives. In terms of religiosity, the influence varies: some feel this concept complements their religious beliefs, while others perceive inconsistencies with Islamic teachings. Factors influencing acceptance include: understanding of the concept, background in religious education, and social environment. The study also emphasizes that although some aspects of the Law of Attraction can be understood psychologically, there are fundamental differences with Islamic teachings that need to be clearly understood. Keywords: Law of Attraction, Social Media, Muslim Generation Z, Religiosity, Social Phenomenon.